A Systematic Review of the Impact of Exposure to Internet-Based Alcohol-Related Content on Young People's Alcohol Use Behaviours. - Gupta, Himanshu; Pettigrew, Simone; Lam, Tina; Tait, Robert (Oxford University Press, 2016)
AIMS: To conduct a systematic review of studies exploring the relationship between exposure to Internet-based alcohol-related content and alcohol use among young people. METHODS: Searches of electronic databases and reference lists of relevant articles were conducted to retrieve studies of relevance up until December 2015. Full texts of the studies that met the inclusion criteria were read, appraised for quality using the Kmet forms and guidelines, and included in this review. RESULTS: Fifteen relevant studies were identified. The included studies were a mix of cross-sectional, longitudinal, experimental and qualitative studies conducted in the USA, the UK, Australia and New Zealand. The age range of the participants involved in these studies was 12-25 years. Included studies employed a variety of study designs and a range of different exposure variables and outcome measures. Studies demonstrated significant associations between exposure to Internet-based alcohol-related content and intentions to drink and positive attitudes towards alcohol drinking among young people. CONCLUSION: Exposure to alcohol-related content on the Internet might predispose young people to patterns of alcohol use by promoting alcohol as a natural and vital part of life. However, the research exploring the influence of this novel form of advertising on young people's alcohol use is emergent, and comprised primarily of cross-sectional studies. To evaluate the direction of the association between exposure to online alcohol-related content and alcohol use, we call for further research based on longitudinal designs. SHORT SUMMARY: From 15 relevant studies identified, this review reports significant associations between exposure to Internet-based alcohol-related content and intentions to drink and positive attitudes towards alcohol drinking among young people, with different influences found at different stages of alcohol use.